Identifying Early Childhood Science Process Skills Through Color Mixing Experimental Activities - Zahrah, Faiqatuz; Winarti, Winarti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Early childhood science learning must be adapted to the child's developmental stage. The science learning stage is still at the stage of recognizing and mixing colors. This research aims to determine the ability to identify science skills in early childhood through experimental activities of mixing colors at Al-Furqan Kindergarten. This research uses descriptive qualitative research. Data collection techniques using observation and documentation. The research results show that children's ability to experiment with science through color mixing activities is very good, marked by children's ability to experiment, namely by observing, classifying, comparing, measuring, communicating and concluding. This is caused by teachers involving children directly in science experiment activities, so that children are more excited and then start doing simple experiments by mixing colors. This science experiment activity through mixing colors goes through a process of preparation, implementation and evaluation. The teacher prepares what is needed for this activity and carries out the activity according to what has been planned, then evaluates what are the shortcomings for carrying out the next science experimental activity. Meanwhile, the science process skills are observing, classifying, comparing, measuring, communicating, experimenting and concluding.